2009
DOI: 10.1111/j.1365-2591.2008.01512.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the strength and radiopacity of Portland cement with varying additions of bismuth oxide

Abstract: Addition of bismuth oxide did not affect the compressive strength of Portland cement. All the bismuth oxide cement mixtures had radio-opacities higher than 3 mm thickness of aluminium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 25 publications
6
21
1
2
Order By: Relevance
“…Bortoluzzi et al 23 used indirect digital technique and found similar results as it was found in the present study using conventional film radiography for 20% addition of Bi 2 O 3 , BaSO 4 and CHI 3 , but significantly higher radiopacity for 20% addition of ZrO 2 . In the previous reports densitometric analysis of radiographic films exhibited the results for TiO 2 , ZnO, BaSO 4 and Bi 2 O 3 additions that corroborate the results of the current study 23,24 . The barium containing materials such as InnoEndo ® (Haraeus-Kulzer, Armonk, NY), Epiphany ® sealer (Pentron clinical technologies), Pulpdent RCS ® (Pulpdent Corporation, Watertown, MA) and Nogenol ® (GC America Inc., Alsip, IL) are reported to appear 44.1%, 9.4%, 17% and 12.5%, respectively, more radiopaque on PSP digital system than on conventional film radiography.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Bortoluzzi et al 23 used indirect digital technique and found similar results as it was found in the present study using conventional film radiography for 20% addition of Bi 2 O 3 , BaSO 4 and CHI 3 , but significantly higher radiopacity for 20% addition of ZrO 2 . In the previous reports densitometric analysis of radiographic films exhibited the results for TiO 2 , ZnO, BaSO 4 and Bi 2 O 3 additions that corroborate the results of the current study 23,24 . The barium containing materials such as InnoEndo ® (Haraeus-Kulzer, Armonk, NY), Epiphany ® sealer (Pentron clinical technologies), Pulpdent RCS ® (Pulpdent Corporation, Watertown, MA) and Nogenol ® (GC America Inc., Alsip, IL) are reported to appear 44.1%, 9.4%, 17% and 12.5%, respectively, more radiopaque on PSP digital system than on conventional film radiography.…”
Section: Discussionsupporting
confidence: 91%
“…The interference of potential radiopacifiers with other physical and biological properties of PC should be further examined. The results of the present and previous studies 24,27 imply, however, that Bi 2 O 3 content may be reduced in MTA from 20% to 10% in order to minimize its adverse effects on material's properties.…”
Section: Discussionmentioning
confidence: 46%
“…For this reason, a radiopacifying component must be associated to PC formulation. Depending on the proportion of the radiopacifier added to PC, there is concern that it could negatively affect the constants of the material, reduce the compressive strength, and consequently modify its biological properties (22,23). For instance, the radiopacifier bismuth oxide (MTA component) can be genotoxic, depending on concentration.…”
Section: Discussionmentioning
confidence: 99%
“…7 As confirmed in prior studies using SEM imaging and energy-dispersive X-ray spectrum (EDX) analysis, Bi 2 O 3 -loaded cement with a 25% additive rate and Portland cement were similar except that the Portland cement lacked bismuth (Hwang et al, 2009). The Bi 2 O 3 additive did not affect the compressive strength of the Portland cement after aging for 28 days (Saliba et al, 2009). During Bi 2 O 3 -loaded cement hydration, bismuth formed part of the structure of the silicate hydrate gel and also affected the precipitation of calcium hydroxide in the hydrated paste (Camilleri, 2007).…”
Section: Mechanical Properties Of Bi 2 O 3 -Loaded Concretementioning
confidence: 89%